12 immigrants who made American entertainment great - Terrell, Brandon, 1978-2021 (Nation of immigrants., 2019)
Presents twelve brief biographies of immigrants who made an impact through their work as American entertainers ranging from John Lennon to Sofia Vergara. Includes a glossary, resources for further information, and color photographs.